A Europa do Conhecimento - Isabel Maria Freitas Valente (História Contemporânea, 2019)
Throughout History, networks of scientists and knowledge exchange have been formed, and scientific mobility has been promoted both at the level of the academy and at political level. In the 1940s the "Europe of mobility" began to be drawn through, among other things, the creation of centers of critical reflection, involving not only academics but also intellectuals and politicians, who would contribute to the design of a "Europe of Education" and, in a broad sense, of a Europe of Knowledge. In this context, this collective volume gathers original contributions that focus on education and citizenship; History books; the ERASMUS program, both the academic and the military; the European credit transfer system; memory and heritage.